The Spirituality of Elementary School Teachers in Indonesia in Teaching Visual Arts - Ramlan, Ramlan (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
It is indicated that art education in Indonesian schools is considered less important by policymakers or curriculum developers compared to other subjects such as mathematics, science, and English. As a result, art teachers in elementary schools often carry out their teaching without seriousness or alignment with the intended learning objectives. This study employs the "Action Research" method, in which elementary school teachers responsible for teaching visual arts are given teaching interventions and then guided through reflection. The findings reveal that after undergoing the intervention, evaluation, and reflection, elementary school teachers experienced an increase in their spirituality when teaching visual arts.